BEYOND REPUTATION: DETERMINANTS OF FINANCIAL PERFORMANCE – EVIDENCE FROM INDONESIA STOCK EXCHANGE - Paulina Y. Amtiran; Yuri S. Faah; Yonas F. Riwu (Universitas Tulungagung, 2026)
This study aims to examine the relationship between assets, market capitalization, company reputation, and stock prices in relation to financial performance. The research sample consisted of 30 companies listed on the Indonesia Stock Exchange, selected using a purposive sampling technique. Data collection was conducted using secondary data from 2017 to 2022. The analysis employed multiple regression analysis with panel data. The results indicate that assets, market capitalization, and stock prices significantly affect financial performance, while the company's reputation index does not have a significant impact. These findings suggest that companies with strong asset values, high market capitalization, favorable stock prices are likely to enhance their financial performance. The study is limited by the small sample size of 30 companies, which may affect the generalizability of the findings. Further researchers are encouraged to use a larger number of samples with different analysis methods. Implications: This study serves as a benchmark for companies assessing their performance and provides valuable insights for investors when making investment decisions.